Income Smoothing: The Role of Growth, Financial Performance, Bonus Plan, and Cash Holding - Budiman, Nita Andriyani; Syaharani, Nova; Ashsifa, Izza (Jurnal Ekonomi dan Bisnis, 2025)
This study examines income smoothing, a form of earnings management where companies report consistent earnings over time, with a focus on the primary consumer goods sector in Indonesia—an industry highly sensitive to investor expectations and exhibiting fluctuating income smoothing practices between 2019 and 2023. The research addresses how firm growth, financial performance, bonus plans, and cash holdings influence the likelihood of income smoothing. Unlike previous studies that generally discuss earnings management more broadly, this paper contributes by specifically exploring income smoothing within a sector and time frame that have received limited empirical attention. Using a quantitative approach, the study employs logistic regression analysis on 175 firm-year observations selected through purposive sampling from companies listed on the Indonesia Stock Exchange. The results show that firm growth and cash holdings do not significantly affect income smoothing, while financial performance has a negative effect and bonus plans have a positive effect, suggesting that internal managerial incentives play a more prominent role than growth or liquidity. The study concludes that income smoothing is primarily driven by internal factors such as bonus schemes, offering important implications for corporate governance practices and the promotion of financial transparency.